مستوى الاهتمام بالخصائص البدنية والقياسات الجسمية أثناء عملية انتقاء رياضيي الجودوفئة الأشبال أقل من 17 سنة - معلوم, لخضر (جامعة الوادي - University of Eloued, 2022)
تهدف الدراسة إلى التعرف على مستوى الاهتمام بالخصائص البدنية والقياسات الجسمية اثناء عملية انتقاء رياضيي الجودو فئة الأشبال أقل من 17 سنة. ولهذا الغرض استخدمنا المنهج الوصفي على عينة متكونة من مربي ومدربي ومستشاري رياضة الجودو لولاية الجزائر، تم اختيارها طريقة عشوائية بسيطة لجمع البيانات استخدمنا أداة استمارة الاستبيان، بعد جمع النتائج ومعالجتها إحصائيا تم التوصل الى أن مستوى الاهتمام بها كان متوسطا حسب وجهة نظر عينة الدراسة وتوجد فروق في مستوى الاهتمام بالخصائص البدنية والقياسات الجسمية اثناء عملية انتقاء رياضي الجودو. الكلمات المفتاحية: الخصائص البدنية؛ القياسات الجسمية؛ الانتقاء؛ الجودو؛ فئة الاشبال. Abstract: The study aims to identify the level of interest in the physical characteristics and anthropometric measures during the selection process of the judo sports for cubs aged less than 17 years old. For this purpose, a descriptive method has been adapted on a random sample made up of educators, trainers, and consulters of judo in Algiers. A questionnaire has been used as a tool to collect data. After collecting the results and treating them statistically, it is concluded that the level of interest according to the study sample was average and there are differences in both, the physical characteristics and anthropometric measurements during the selection process of the judo
The basic factors for good selection in judo sport Analytical approach to both physical characteristics and body measurements Cubs under 17 years old Category
مقال
Keywords: الخصائص البدنية، القياسات الجسمية، الانتقاء، الجودو، فئة الأشبال; physical characteristics, anthropometric measurements , selection, judo, cubs.